Efeito do fungo micorrízico arbuscular e do vermicomposto na fitorremediação do cobre em solo arenoso - Santana, Natielo Almeida (2014)
Introduction and objectives: Arbuscular mycorrhizal fungi and vermicompost may decrease the deleterious effects of copper on plants. The goal of the present study was to evaluate the effect of inoculation with the fungus Rhizophagus clarus and the addition of grape bagasse vermicompost on phytoremediation by Canavalia ensiformis of a sandy soil with high Cu concentration. Methods: Soil was contaminated with 100 mg Cu kg-1, fertilized with five levels of vermicompost, and cultivated with C. ensiformis with and without inoculation with Rhizophagus clarus. Availability of Cu and other nutrients in the soil and in the soil solution, shoot and root accumulation of Cu and other nutrients, plant growth, and Cu phytotoxicity using photochemical efficiency, concentration of photosynthetic pigments, and oxidative stress enzyme activities as indicators of Cu phytotoxicity were evaluated. Results: Phytostabilization showed better performance with the addition of the vermicompost level equivalent to 20 mg P kg-1 and in the presence of R. clarus. Phytoextraction was higher with the addition of the vermicompost level equivalent to 40 mg P kg-1 and without R. clarus inoculation. However, C. ensiformis was not a good phytoextractor. Conclusions: The system C. ensiformis vermicompost R. clarus exhibited potential for Cu phytostabilization in sandy soils.